2016
DOI: 10.18632/oncotarget.7241
|View full text |Cite
|
Sign up to set email alerts
|

Molecular spectrum of TP53 mutations in plasma cell dyscrasias by next generation sequencing: an Italian cohort study and overview of the literature

Abstract: The prevalence of TP53 mutations greatly varies between tumor types; in multiple myeloma (MM) they were rarely detected at presentation, while increased frequency was reported with disease progression. Using next-generation sequencing, we analyzed TP53 exons 4-9 in a large representative cohort comprising patients with MM at diagnosis and more aggressive forms of plasma cell (PC) dyscrasia, identifying mutations in 4/129 (3%) MM, 6/24 (25%) primary PC leukemia, and 2/10 (20%) secondary PC leukemia cases. A sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
3
26
0
1
Order By: Relevance
“…In MM, TP53 mutations are uncommon at diagnosis (~8%) [28,29,30], although the incidence increases in the advanced stages of the disease, suggesting its essential role in MM progression [31,32]. These findings have also been confirmed by using massively parallel sequencing [16,33]. Thus, only 8% of MM patients analyzed by Lohr et al showed missense TP53 mutations, two of which corresponded to hotspot residues R273 and R248 within the DNA-binding domain, and commonly mutated in other human tumors [33].…”
Section: Alterations Of Tp53 Gene In Human Cancers and Particularlmentioning
confidence: 99%
See 4 more Smart Citations
“…In MM, TP53 mutations are uncommon at diagnosis (~8%) [28,29,30], although the incidence increases in the advanced stages of the disease, suggesting its essential role in MM progression [31,32]. These findings have also been confirmed by using massively parallel sequencing [16,33]. Thus, only 8% of MM patients analyzed by Lohr et al showed missense TP53 mutations, two of which corresponded to hotspot residues R273 and R248 within the DNA-binding domain, and commonly mutated in other human tumors [33].…”
Section: Alterations Of Tp53 Gene In Human Cancers and Particularlmentioning
confidence: 99%
“…Thus, only 8% of MM patients analyzed by Lohr et al showed missense TP53 mutations, two of which corresponded to hotspot residues R273 and R248 within the DNA-binding domain, and commonly mutated in other human tumors [33]. In contrast, the frequency of TP53 mutations increases up to 25% in plasma cell leukemia [16]. Furthermore, longitudinal analysis of MM patients reveals that TP53 mutations are often acquired at relapse [16].…”
Section: Alterations Of Tp53 Gene In Human Cancers and Particularlmentioning
confidence: 99%
See 3 more Smart Citations